Quality teacher : national aspiration to develop human capital for a knowledge-based economy - Hamzah, Mohd Sahandri Gani; Abdullah, Saifuddin Kumar (EuroJournals, 2009)
Teaching is one of the most challenging and one of the most important jobs in our society. Teachers play the role of producing knowledgeable students with good personality. Quality of a teacher is the most important school-related factor influencing student achievement. In order to solve the problems of shortage of teachers, government had recruited many teachers with different qualification. Government should make sure that the teachers meet the minimum requirement before letting them to enter the education field. We should not only focus on the quantity and neglect the quality of the teachers. Qualities of teachers should be measured from five categories which had stated in the National Education Philosophy- Physical, emotion, spiritual, intellectual and social. Physically healthy, high emotional intelligence, high spirituality, high intellectual and good social skills are the criteria of a quality teacher. Test should be conducted based on these aspects, such as IQ test for intellectual and EQ test for emotion, to determine the quality of a teacher. Only those who achieve good results in all these aspects are considered as a quality teacher. Better pay as well as promotion should be given to them.